Alzheimer’s disease neuropathological change and loss of matrix/neuropil in patients with idiopathic Normal Pressure Hydrocephalus, a model of Alzheimer’s disease - Libard, Sylwia; Alafuzoff, Irina (Acta neuropathologica communications, 2019)
Here, we assessed unique brain tissue samples, obtained from living subjects with idiopathic Normal Pressure Hydrocephalus (iNPH). Our cohort of 95 subjects with age ranging from 75 to 79 years, displayed a high prevalence of β-amyloid (Aβ) and hyperphosphorylated τ (HPτ) pathology (63 and 61%, respectively) in a frontal cortex biopsy obtained during shunt operation. These lesions, i.e., Alzheimer’s Disease Neuropathologic Change (ADNC), increased within 5 years and were more frequent in females. The extent of HPτ pathology was sparse, primarily seen as neurites and stained dots. Noteworthy, concomitant pathology was seen in 49% of the whole cohort, indicating a severity of ADNC corresponding to a low/intermediate level following the current recommendations. This observation is predictable as based on previous publications a substantial number of subjects with iNPH over time develop AD. Thus, iNPH can be considered as a model of AD. We noted a surprisingly remarkable neuronal preservation assessing Neuronal Nuclei (NeuN) in parallel with a substantial depletion of matrix/neuropil. This finding is intriguing as it suggests that loss of matrix/neuropil might be one of the first lesion of ADNC but also a hallmark lesion of iNPH. The latter observation is in line with the enlarged ventricles, a cardinal feature of iNPH. Furthermore, a positive correlation was observed between the extent of Aβ and NeuN but only in females indicating a neuronal preservation even when Aβ pathology is present. The assessment of a surgical biopsy as described here is certainly informative and thus it is surprising that a neuropathologic assessment in the setting of iNPH, while inserting a shunt, is seldom performed. Here, we observed ADNC and surprisingly remarkable neuronal preservation in a substantial number of iNPH subjects. Thus, these subjects allow us to observe the natural course of the disease and give us an opportunity for intervention at the earliest stages of AD, prior to severe neuronal damage.